The Role of Le Balet Comique in Forging the Stuart Masque Part 2 Continuation - Daye, Anne (Edinburgh: Edinburgh University Press, 2015)
RESUMEN: Following the discussion in Part 1 (Dance Research 32.2 2014, 185-207) of the use made by the Jacobean court of Le Balet Comique (McGowan 1982) to frame innovation in the masque, this article will explore two further examples of the continuing use of the text. The overt adoption of features of Le Balet Comique for Tempe Restored (1632, Aurelian Townshend and Inigo Jones) brought French practice into play once more for the Caroline masque. Following in his father's footsteps, Charles 1 was able to bring to the masque his personal skill as a dancer and the participation of his young and beautiful French queen Henrietta Maria. From the re-launch of the court masque in 1631, until the break-up of the Whitehall court in 1640, both retrospective and innovative practices were pursued. Although this was a new reign, a strong element of continuity prevailed in the court personnel serving the masque. Acting as artistic director, Inigo Jones was now firmly in control of masque concepts, pursuing a design process of imaginative imitation based on Renaissance practice. In collaboration with individuals among the music and dance artists, Jones had been intimately involved in adapting features of the ballet in devising The Masque of Queens of 1609. That Le Balet Comique formed the basis for Tempe Restored is made very plain in the published text. The influence of the 1581 ballet on A Masque presented at Ludlow Castle 1634 (known as Comus) by John Milton can only be discerned by analysing the performance conditions of a work that is now published as a poem. Once again the Circe persona takes the stage, this time in masculine form as Comus. I argue here that the link between the two is the personnel of Tempe Restored. An analysis of the original performance of Comus draws on understanding of elite dance practice of the day leading to new insights into this innovative masque.